Thermoacoustic Properties of Binary Liquid Mixtures of Sulfolane with Aniline, N,N-Dimethylaniline and N,N-Diethylaniline at Different Temperatures and Atmospheric Pressure - Aftabuzzaman, Mohammad; Monirul Islam, Mohammad; Nasiruddin; Rahman Rima, Farhana; Nazrul Islam, Mohammad; Azhar Ali, Mohammad (Asian Journal of Chemistry, 2021)
Densities and sound velocities of the binary liquid mixtures of sulfolane + aniline, sulfolane + N,N-dimethylaniline, sulfolane + N,N-diethylaniline over the whole range of composition and their pure component were measured at temperatures (T = 303.15, 308.15, 313.15 K) and atmospheric pressure. A high precision vibrating-tube densitometer was used for the measurements. From the measured values, excess adiabatic compressibility (βsE), excess sound velocity (uE), excess internal pressure (PiE) and deviation of surface tension (Δγ) were calculated for each of the systems. The excess properties and surface tension deviation were fitted to the Redlich-Kister equation. All these properties have been discussed in terms of molecular interactions.